Geochemical impact assessment of produced water of Sadqal oil and gas field on the soil surrounding the storage ponds in Fateh Jang area, Punjab, Pakistan - Khan, Said Akbar; Khan, Hizbullah; Ahmad, Imtiaz; Ishtiaq, Muhammad; Khan, Asad (Journal of Himalayan Earth Sciences, 2015)
Composite soil samples were collected at different distance from eastern, western and southern sides of the produced water ponds of Sadqal oil and gas field Fateh Jang, Punjab, Pakistan to assess the anions, cations and heavy metal concentrations. The concentrations of sodium (Na), potassium (K), calcium (Ca+²), magnesium (Mg+²), chloride (Cl‾), florid (F‾), sulfate (SO4‾2), nitrate (NO3‾) and nitrite (NO2‾) were determined by using Ion chromatography (Metrohm, 800 series). Heavy metal concentrations i.e. chromium (Cr), manganese (Mn), cadmium (Cd), zinc (Zn), copper (Cu), lead (Pb), nickel (Ni) and iron (Fe) were analyzed using Atomic absorption spectrophotometer. The results were compared with reference soil sample of the study area. It was found that maximum parameters of soil samples collected from the surrounding of ponds were high in concentration as compared to that of reference soil samples. A consistent decrease of most of the cations, anions and heavy metals was noticed with increasing distance from the ponds. The soil proximal to the ponds is highly contaminated and can pose health related threats to the human beings and may also cause damaging effects on the plants of the study area.